Material characterization and device design of TiNx infrared microemitter - Wang, Jun Min. (2008)
This thesis systematically studies the electrical and thermal properties of TiN films deposited by the filtered arc deposition (FAD) method. The properties of deposited TiN films are analyzed by means of multiple characterization tools.